Audience Engagement in Live Streaming: An Analysis of Gratifications Sought and Obtained in iShowSpeed's Live Stream in Indonesia - Patria, Rully; Saragih, Dr,M.Si, Nurhayani (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
This study analyzes audience engagement in iShowSpeed’s live streaming in Indonesia using the Uses and Gratifications (U&G) theory. The focus is on comparing Gratifications Sought (GS), or the needs expected by the audience, with Gratifications Obtained (GO), or the satisfaction they experience. A mixed-methods approach was employed, combining qualitative and quantitative analysis of viewer comments and the creator’s conversation transcripts. Comments were categorized into four U&G needs: entertainment, social interaction, personal identity, and information. Results show that entertainment and social interaction dominated, while information and personal identity, though less prominent, still contributed significantly. No gap was found between GS and GO, indicating that the creator’s interaction effectively fulfilled audience needs. This study reinforces the relevance of U&G theory and provides practical insights for content creators to design engaging experiences and build loyal audience communities.